Magnetic field effects on in-medium [Upsilon] dissociation - Hölck, Johannes; Nendzig, Felix; Wolschin, Georg (5th International Conference on New Frontiers in Physics, 2017)
The electromagnetic fields during relativistic heavy ion collisions are calculated using a simple model which characterises the emerging quark-gluon medium by its conductivity only. An estimate of the average magnetic field strength experienced by the bb̄ mesons produced in the collision is made. In a sufficiently strong magnetic field, the individual spins of bb̄ mesons can align with the field leading to quantum mixing of the singlet and triplet spin configurations. The extent of this intermixture, however, is found to be negligible at field strengths occurring in heavy ion collisions at LHC energies.
Im Titel wird "Upsilon" als griechischer Buchstabe dargestellt
Gesehen am 02.09.2020